Lembaga Jaminan terhadap Hak Milik Atas Tanah - Meita Djohan Oelangan (Universitas Bandar Lampung (UBL), 2011)
The Mortgage is important as one of the security institutions which capable to providelegal certainty for the parties concerned in the provision of necessary funds for debtrepayment. The problem is mortgage granting registration requirement as a form ofsecurity institutions of property rights over land. The approach in this research is anormative juridical approach. Secondary data obtained from the literature study.Qualitative analysis of the data is done. Based on the research results can be seenthat the registration which is charged to the Mortgage of Land Property Rights isabsolutely necessary based on an agreement before a notary public with specificspecialties eligible entitlements dependent on the subject, and the publicityrequirements of the registration of Mortgage on the Land Office to ensure legalcertainty.